Optimization of germination time and temperature to maximize the content of bioactive compounds and the antioxidant activity of purple corn (Zea mays L.) by response surface methodology - Paucar-Menacho, Luz María (2017)
The objective of this study was to optimize germination time and temperature for maximizing the content of γ-aminobutyric acid (GABA), total phenolic compounds (TPC), and antioxidant activity in purple corn sprouts by using Response Surface Methodology (RSM). The phenolic composition of purple corn sprouts obtained in the optimal conditions was analyzed by HPLC-DAD-ESI/MS. Temperature of 26 °C and time of 63 h were found to be the optimal germination conditions since they enhanced 3.5-fold GABA content compared with seeds. These conditions, however, reduced ∼30 and ∼15% TPC and antioxidant activity, respectively, in purple corn. The models developed showed high coefficients of determination, demonstrating their adequacy to explain the variations in experimental data. Sprouts obtained in the optimal conditions presented anthocyanins as the most abundant phenolic class, detected mainly as cyanidin, pelargonidin, and peonidin glycosides or their malonyl derivatives. Hydroxycinnamic acids derivatives and flavonols were detected as minor compounds. Thus, germination at 26 °C for 63 h can be considered as an innovative strategy for diversifying the utilization of purple corn, providing at the same time sprouts with high levels of phytochemicals. Purple corn sprouts may constitute promising health-promoting foods.